2013
DOI: 10.1002/adfm.201203065
|View full text |Cite
|
Sign up to set email alerts
|

High‐Mobility n‐Type Organic Transistors Based on a Crystallized Diketopyrrolopyrrole Derivative

Abstract: A new high-performing small molecule n-channel semiconductor based on diketopyrrolopyrrole (DPP), 2,2 ′ -(5,5 ′ -(2,5-bis(2-ethylhexyl)-3,6-dioxo-2,3,5,6tetrahydropyrrolo[3,4-c]pyrrole-1,4-diyl)bis(thiophene-5,2-diyl))bis(methan-1-yl-1-ylidene)dimalononitrile (DPP-T-DCV), is successfully synthesized. The frontier molecular orbitals in this designed structure are elaborately tuned by introducing a strong electron-accepting functionality (dicyanovinyl). The well-defi ned lamellar structures of the crystals displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…Although solution processable p-type OSCs with high mobility have been successfully developed with a wide range of molecular designs, [6][7][8][9][10][11][12] only few n-type OSCs have shown mobilities > 0.5 cm 2 V −1 s −1 in solution-processed devices. [13][14][15][16][17] Perylene and naphthalene tetracarboxylic bisimides (PDIs and NDIs) were among the most used structures from the early stages in the development of n-type OSCs due to the ease of synthesis, chemical stability and high electron accepting properties. [18][19][20][21][22][23][24] Moreover, perfluorophenyl and perfluoroalkyl-substituted OSCs have also been widely developed by incorporating thiophene/phenylene backbones.…”
Section: Introductionmentioning
confidence: 99%
“…Although solution processable p-type OSCs with high mobility have been successfully developed with a wide range of molecular designs, [6][7][8][9][10][11][12] only few n-type OSCs have shown mobilities > 0.5 cm 2 V −1 s −1 in solution-processed devices. [13][14][15][16][17] Perylene and naphthalene tetracarboxylic bisimides (PDIs and NDIs) were among the most used structures from the early stages in the development of n-type OSCs due to the ease of synthesis, chemical stability and high electron accepting properties. [18][19][20][21][22][23][24] Moreover, perfluorophenyl and perfluoroalkyl-substituted OSCs have also been widely developed by incorporating thiophene/phenylene backbones.…”
Section: Introductionmentioning
confidence: 99%
“…Suraru et al has also reported a p-channel small molecular DPP derivative functionalized with cyanyl group for OFETs with field-effect mobility of 0.7 cm 2 /Vs [18]. OFETs based on n-channel DPP-T-DCV (functionalized with dicyanovinyl group) has been reported by Yoon et al with an electron mobility of 0.96 cm 2 /Vs (single crystalline) and 0.64 cm 2 /Vs (film) [19]. Most efforts for DPP small molecule research has been directed toward the introduction of various aromatic moiety/chromophores as an end capping unit to the core in order to investigate the effect on device characteristics.…”
Section: Introductionmentioning
confidence: 92%
“…53,56 As shown in Fig. 2a, the absorption spectrum is characterized by two principal absorptions, around 413 nm due to the thiophene-benzene portion of the molecule and another, more intense band at 613 nm with a vibronic absorption shoulder at 651 nm, likely involving the DPP unit together with the surrounding thiophenes.…”
Section: Photophysical Properties and Homo/lumo Energiesmentioning
confidence: 99%